THE EFFECT OF TAX INCENTIVES, GROWTH OPPORTUNITIES, AND FINANCIAL DISTRESS ON ACCOUNTING CONSERVATISM: (Empirical Study on Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange for the 2017-2021 Period) - Meilia Echa Narenda; Intan Rahma Sari (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to give empirical evidence of the effect of Tax Incentives, Growth Opportunities, and Financial Distress on Accounting Conservatism. This work used quantitative approaches, and the data that are analyzed are secondary data. The population of this study consists of manufacturing enterprises that fall under the food and beverage sub-sector and are listed on the Indonesia Stock Exchange for the period of 2017-2021. This study used purposive sampling to determine the sample. The amount of sample data obtained is 50, and it was obtained by taking a sample from 10 different companies over a period of five years. When doing tests, there are sometimes extreme values, which can result in outliers in the sample data. This study uses several test to analyze the data, namely multiple linear regression descriptive statistical test, linear analysis of panel data, Fixed Effect Model as the model selection test, classical assumption test, multiple linear test, and hypothesis testing with the assistance of data processing Eviews version 9. The results of this study indicates that incentives Taxes, Growth Opportunities, and Financial Distress simultaneously have a significant effect on Accounting Conservatism. Tax incentives have no significant effect on Accounting Conservatism. Growth Opportunities have a significant effect on Accounting Conservatism. Financial Distress has no significant effect on accounting conservatism.